2001
DOI: 10.1897/1551-5028(2001)020<1951:tgshaa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Garden Snail (Helix Aspersa) as a Bioindicator of Organophosphorus Exposure: Effects of Dimethoate on Survival, Growth, and Acetylcholinesterase Activity

Abstract: The garden snail (Helix aspersa) is currently used as bioindicator of metallic pollution. Our objective was to extend its use to organic chemicals by studying the effects and tissue concentrations of the organophosphorus pesticide dimethoate following dietary uptake. After exposure for four weeks to increasing doses of pesticide in the diet, the median lethal concentration (LC50) was determined to be 3,700 microg/g food. Clinical signs indicated a no-observed-effect concentration of 100 microg/g and a lowest-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…In addition, Coeurdassier et al (2001Coeurdassier et al ( , 2002 mentioned that the anti-AChE pesticide (dimethoate) induced the reduction in the growth of H. aspersa and attributed that to the inhibitory effect of this compound on AChE activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Coeurdassier et al (2001Coeurdassier et al ( , 2002 mentioned that the anti-AChE pesticide (dimethoate) induced the reduction in the growth of H. aspersa and attributed that to the inhibitory effect of this compound on AChE activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bars represent standard deviation Beeby and Richmond 2002;Scheifler et al 2002;de Vaufleury et al 2006;Hispard et al 2007), few studies have reported such phenomenon for pesticides. Coeurdassier et al (2001) found a low accumulation of dimethoate in H. aspersa tissues exposed to artificially contaminated food and Schuytema et al (1994) did not find atrazine or azinphosmethyl bioaccumulation in the same species, probably in relation with the degradation of chemicals in tissues and/or to a low sensitivity of the analytical methods. Glyphosate accumulation was not expected due to the chemical characteristics of the molecule, such as for instance its high solubility in water (10,500 mg l −1 ) and its low K ow (log K ow =−3.1).…”
Section: Fate In and Effects Of Herbicides On Snails And Comparison Wmentioning
confidence: 97%
“…Concentrations in snails given in milligrams per kilogram fw were converted into dw by considering 80% of water content in snails (Gomot 1998). Calculation of BAF (dw/dw) of a pesticide by snail is usually expressed by considering the tissue concentrations in dry weight (Coeurdassier et al 2001). It allows minimizing the influence of variability of water content in snails following the humidity of the medium and facilitating comparisons of data of experiments performed in various environmental conditions.…”
Section: Observation Of the Genital Apparatus And Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have used other gastropods to monitor mercury exposure (Bertani et al, 1994). Coeurdassier et al (2001) consider other groups of contaminants (pesticides, polycyclic aromatic hydrocarbons (PAH), etc). Pihan and Gomot de Vaufleury (2000) used 2 terrestrial snail species (H. aspersa aspersa and H. pomatia) to assess the contamination of an industrial waste dump site (pollution by heavy metals) and to monitor the efficiency of in situ remediation techniques.…”
Section: Introductionmentioning
confidence: 99%